IMPLEMENTASI ELDERLY FITNESS EXERCISE DENGAN NYERI SENDI OSTEOARTHRITIS (OA) DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Sitompul, Desi; Pratama, Muchti Yuda; Olivia, Nina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Joint pain caused by osteoarthritis (OA) is a common health condition among the elderly, often resulting in decreased mobility and reduced quality of life. This condition leads to limitations in daily activities and increases the risk of complications due to prolonged immobility. One of the non-pharmacological interventions that can be applied is Elderly Fitness Exercise, which aims to improve physical fitness, reduce pain, and maintain joint flexibility. This study aims to describe the implementation of Elderly Fitness Exercise in elderly individuals with osteoarthritic joint pain. The research employed a case study design using the nursing care process approach, which includes assessment, diagnosis, planning, implementation, and evaluation. The subjects were two elderly individuals with knee osteoarthritis experiencing moderate pain. Data were collected through interviews, observation, physical examination, as well as documentation using pain assessment scales and fitness evaluation sheets. The intervention was conducted over six consecutive days in February 2025. The findings indicate a reduction in pain levels, improvement in mobility, and increased joint flexibility following the consistent implementation of the exercise. This study concludes that Elderly Fitness Exercise is an easily applicable intervention to relieve joint pain and help improve physical fitness in elderly individuals with OA